Kompetensi Pedadogik Guru dalam Capaian Pembelajaran Partisipasi Aktif Siswa dalam Kegiatan Pembelajaran - Nazwa Clarissa; Otista C A Sembiring; Peter Patiangbanua Purba; Rendi Jonatan Lumban Gaol; Salwa Khairani Tarigan; Suci Rohani Br Panjaitan; Jamaludin Jamaludin; Sri Yunita (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This study aims to examine the role of teacher pedagogical competence in increasing students' active participation in learning. With the challenges of the digital era, teachers need to optimize technology and innovative learning methods such as the student-centered learning approach and local cultural integration. This descriptive qualitative study was conducted at UPT SMP Negeri 10 Medan, using observation, interviews, and literature studies. The results show that interactive learning methods and the use of digital media can increase student participation. However, teachers face challenges such as differences in student understanding and lack of self-confidence. Teachers need to act as facilitators and motivators to create a supportive learning environment.